Natural radioactivity measurement in pumice samples used raw materials in Turkey - Turhan, Şeref; Yücel, H.; Gündüz, L.; Şahin, Ş.; Vural, M.; Parmaksız, A.; Demircioğlu, B. (Applied Radiation and Isotopes, 2006)
The activity concentrations of 232Th, 226Ra, and 40K in different pumice samples have been determined by high-resolution g-ray spectrometry using a 110% HpGe detector. The radium equivalent activities (Raeq), external hazard index (Hex), and internal hazard index (Hin) associated with the natural radionuclides and representative level index (Igr) are calculated to assess the radiation hazard of the natural radioactivity in the pumice samples. The mean values of the measured radioactivity concentrations of 232Th, 226Ra, and 40K for pumice samples from the region of lakes (ROL) are 232.478.0, 196.977.8, and 1325.8720.4 Bq kg1 and for pumice samples from C- ukurova region (C- R) 16.374.0, 16.174.9, and 479.77170.4 Bq kg1 , respectively. The calculated Raeq values vary from 435.9712.5 to 883.6741.5 Bq kg1 with a mean of 630.9720.2 Bq kg1 for the ROL samples and from 49.773.3 to 101.977.2 Bq kg1 with a mean of 76.3723.7 Bq kg1 for the C- R samples. For the ROL samples, Raeq are above the limit of 370 Bq kg1 , equivalent to external g dose of 1.5 mSv yr1 , recommended for the safe use of construction materials by NEA–OECD, while for the C- R samples, Raeq values are lower than the limit
Keywords: Radioactivity concentration; Radium equivalent; Health hazard indices; Radium; Thorium; Potassium; g-ray spectrometer; Pumice